1982
DOI: 10.1038/bjc.1982.167
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous malignant melanoma in Scotland

Abstract: Summary.-In view of the concern over the rising incidence of malignant melanoma in many parts of the world, and the suggestion that emigrants of Scottish and Irish descent have a higher incidence of melanoma in North America and Australia, a Scottish Melanoma Group has been formed to study epidemiological, pathological and therapeutic aspects of the tumour. In 1979, 260 histologically proven primary cutaneous malignant melanomas of the skin presented. This represents an incidence of 5 1/105 for Scotland as a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Most of the previous studies were high-volume studies; hence, they reported more cases at each site. In spite of the relatively small number of cases reviewed in the present study, when categorized into different sites, this study is in agreement with the fact that the most frequent site for malignant melanomas in males is the upper back, and in females it is the lower leg and ankle, even across populations from different geographic areas (20,25,26,27,28).…”
Section: Discussionsupporting
confidence: 69%
“…Most of the previous studies were high-volume studies; hence, they reported more cases at each site. In spite of the relatively small number of cases reviewed in the present study, when categorized into different sites, this study is in agreement with the fact that the most frequent site for malignant melanomas in males is the upper back, and in females it is the lower leg and ankle, even across populations from different geographic areas (20,25,26,27,28).…”
Section: Discussionsupporting
confidence: 69%
“…In the British Isles a female to male ratio for melanoma of approximately two-to-one has been reported (Lee & Storer, 1980;MacKie & Hunter, 1982) compared with only a small female excess in most other parts of the world. It may be that this marked sex differential is obliterated in other countries by a larger number of predominantly 'solar' cases in those areas.…”
Section: Thicknessmentioning
confidence: 99%
“…Shaw et al, 1980;Balch et al, 1978;MacKie & Hunter, 1982;Eastwood & Baker, 1983. This could be due to more aggressive disease but is more likely related to diagnostic delay associated with decreased public and professional awareness of the disease.…”
Section: Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with vertical growth-phase primary tumours, Breslow thickness at presentation is the most important single prognostic indicator in CMM (MacKie et al, 1985;Masback et al, 2001), with 5 years survival values ranging from 93% for tumours < 1.5 mm thick, compared with 67% for 1.5 -3.49 mm tumours, to 37% for tumours > 3.5 mm thick (MacKie et al, 1992). Therefore, investigation of ICAM-1 genotypes in terms of tumour Breslow thickness was of particular interest.…”
Section: Discussionmentioning
confidence: 99%